Psychological treatment and comprehensive damage repair in the event of family violence: restorative justice (Revista de Investigaciones Universidad del Quindío, 2021)
Restorative justice is a tool for the parties involved in a judicial process to obtain compensation for the damaged property. This article aims to describe the scope of the victims involved in a process of family violence, limited to the cases where they cohabit as children, boys, girls and adolescents, before the Control Judge in the situations of arrival at the alternate exit of conditional suspension, is officially imposed regardless of the other conditions to be met during the same, the psychological treatment established in article 195, section VII of the National Code of Criminal Procedures. Considering that the crime of family violence protects the harmonious coexistence of the family bond, not of civil kinship relations, it is an entity consisting of the psyche of the direct and indirect victims, the latter due to the collateral damage of the execution of the same. In that order of ideas, the protection of the rights of the victim cannot be restricted only to the direct victim, but a repair of the damage to the psyche of those who are injured by parental alienation is obtained, the right of access to the Justice. In this regard, the fact that it is not possible to speak of restorative justice in a conditional suspension of proceedings is addressed and justified, without the informal observance of psychological treatment.
Keywords: right to family; protection; disorders; conditional suspension; indirect victims